2014
DOI: 10.1177/1066480714564381
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Impact of Police Work on Marital Relationships

Abstract: Police work creates unique marital difficulties. There are many factors that add stress to police officers' marriages, including shift work, long hours and unconventional schedules, divided commitment between work and family roles, and perceived personality changes among officers. When police officers carry work-related stress and behaviors into the home, they may experience difficulties in their family relationships. Unfortunately, relatively few researchers have investigated the impact of police work on spou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
67
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(74 citation statements)
references
References 43 publications
1
67
0
1
Order By: Relevance
“…Research has shown that LEOS are susceptible to secondary trauma, or vicarious trauma (Kirschman, 2018), in addition to occupational stress caused by: an irregular work schedule, personality changes (Roberts & Levenson, 2001), bringing work stress home (Karaffa et al, 2015), the stigma attached to seeking mental health services (Karaffa & Koch, 2016), and higher alcohol use to cope with stress (Menard & Arter, 2013). Studies completed with first responders, police, fire, and medical, suggests a high percentage of workers bring home their occupational stress and it plays a significant role in how they interact in their personal lives (Roberts & Levenson, 2001;Fay, Kamena, Benner, & Buscho, 2006;Karaffa et al, 2015;Porter & Henriksen, 2016;Kirschman, Kamena, & Fay, 2013). The law enforcement community is a culture within itself, is extremely hard for an outsider to develop trust without being a member, and studies have shown how this separate culture can provide additional strain on the family (Roberts & Levenson, 2001;Karaffa et al, 2015).…”
Section: Purpose Of the Studymentioning
confidence: 99%
See 3 more Smart Citations
“…Research has shown that LEOS are susceptible to secondary trauma, or vicarious trauma (Kirschman, 2018), in addition to occupational stress caused by: an irregular work schedule, personality changes (Roberts & Levenson, 2001), bringing work stress home (Karaffa et al, 2015), the stigma attached to seeking mental health services (Karaffa & Koch, 2016), and higher alcohol use to cope with stress (Menard & Arter, 2013). Studies completed with first responders, police, fire, and medical, suggests a high percentage of workers bring home their occupational stress and it plays a significant role in how they interact in their personal lives (Roberts & Levenson, 2001;Fay, Kamena, Benner, & Buscho, 2006;Karaffa et al, 2015;Porter & Henriksen, 2016;Kirschman, Kamena, & Fay, 2013). The law enforcement community is a culture within itself, is extremely hard for an outsider to develop trust without being a member, and studies have shown how this separate culture can provide additional strain on the family (Roberts & Levenson, 2001;Karaffa et al, 2015).…”
Section: Purpose Of the Studymentioning
confidence: 99%
“…Studies completed with first responders, police, fire, and medical, suggests a high percentage of workers bring home their occupational stress and it plays a significant role in how they interact in their personal lives (Roberts & Levenson, 2001;Fay, Kamena, Benner, & Buscho, 2006;Karaffa et al, 2015;Porter & Henriksen, 2016;Kirschman, Kamena, & Fay, 2013). The law enforcement community is a culture within itself, is extremely hard for an outsider to develop trust without being a member, and studies have shown how this separate culture can provide additional strain on the family (Roberts & Levenson, 2001;Karaffa et al, 2015). This culture is a barrier to community members seeking support and can cause isolation.…”
Section: Purpose Of the Studymentioning
confidence: 99%
See 2 more Smart Citations
“…But, as Karaffa et al. (2015) demonstrate, officers soon experience “emotional detachment from other aspects of daily life that are unrelated to the job” (p. 122). For example, in a blog post for Badgeoflifecanada.org, an organization dedicated to improving the health of current and former police officers, a retiree, whom we will call Mark, wrote:
I am alone with my thoughts, my memories and I'm left trying to make some sense out of this ….
…”
Section: Emotional Role Residualmentioning
confidence: 99%